(untitled) (Innovate Conferences, 2025)
This article examines the theoretical aspects of selected eco-physiological traits of durum wheat (Triticum durum) under global drought conditions. It addresses the physiological mechanisms and adaptive responses that enable the crop to survive and maintain productivity under limited water availability. The discussion includes drought tolerance strategies such as osmotic adjustment, stomatal regulation, antioxidant activity, and changes in photosynthetic efficiency. Attention is also given to the role of morphological adaptations, including root system architecture and leaf surface characteristics, as well as the impact of drought stress on grain quality and yield. By integrating insights from plant physiology, agronomy, and environmental science, the article provides a foundation for developing sustainable management practices and breeding programs aimed at improving durum wheat resilience in arid and semi-arid regions.